Preparation of professional engineers for quality management - Goh, T.N (Philippine Engineering Journal)
By virtue of their involvement in product design, manufacture, testing and servicing, engineers constitute the majority of professionals whose work has direct relation to quality. However, the traditional approach to education of professional engineers tends to impact concepts and attitudes that do not necessarily lead to the kind of perspective needed for effective quality management. The deductive learning process in analysis and design, while necessary in general engineering education, is not sufficient for quality management which calls for appreciation and comprehension of uncertainty phenomena in the physical world, proficiency in inductive reasoning, and an adequate understanding of human behaviour. An appropriate orientation in university curriculum is necessary, as mass production of engineering graduates need to man the many technical positions created in a newly industrialized society, will not be sufficient by itself to guarantee the generation of consistently high quality products and services, the mark of a truly advanced economy. Other aspects of education for quality management are discussed, and possible measures are suggested for ensuring quality consciousness and competence in the new generation of engineers.